Effects of transcranial direct current stimulation on motor skills learning in healthy adults through the activation of different brain regions: A systematic review - Qi, Shuo; Liang, Zhiqiang; Wei, Zhen; Liu, Yu; Wang, Xiaohui (Frontiers in Human Neuroscience, 2022)
Objective: This systematic review aims to analyze existing literature regarding the effects of transcranial direct current stimulation (tDCS) on the motor skills learning of healthy adults and discuss the underlying neurophysiological mechanism that influences motor skills learning. Methods: This systematic review has followed the recommendations of the Preferred Reporting Items for Systematic reviews and Meta-Analyses. The PubMed, EBSCO and Web of Science databases were systematically searched for relevant studies that were published from database inception to May 2022. Studies were included on the basis of the Participants, Intervention, Comparison, Outcomes and Setting inclusion strategy. The risk of bias was evaluated by using the Review manager 5.4 tool. The quality of each study was assessed with the Physiotherapy Evidence Database (PEDro) scale. Results: The electronic search produced 142 studies. Only 11 studies were included after filtering. These studies performed well in terms of distribution, blinding availability and selective reporting. They reported that tDCS significantly improved motor skill learning. Conclusion: The included studies demonstrated that tDCS can help healthy adults to improve the motor skills learning by activating different brain regions, such as the left primary motor cortex, left dorsolateral prefrontal cortex and right cerebellum. However, the number of included studies was limited, and the sample sizes were small. Therefore, additional studies are urgently needed to validate the results of current studies and further explore the underlying neurophysiological mechanisms of tDCS in the future.